REVIEW OF BLOOD CROSS-MATCH ORDERING AND TRANSFUSION PRACTICES FOR ELECTIVE HYSTERECTOMIES AT SAINT PAUL’S HOSPITAL MILLENNIUM MEDICAL COLLEGE: FIRST STEP TOWARDS A MAXIMUM SURGICAL BLOOD ORDERING SCHEDULE - K, Lemma; T., Menna; D., Bekele (Ethiopian Journal of Reproductive Health, 2018)
ABSTRACTBACKGROUND: Requesting blood before surgery is a common practice. Studies show that majority of bloodrequested by surgeons are not utilized and this over ordering practices of blood will create a burden on the transfusionservice. It diverts blood from the pool and makes it unavailable for other needy patients.OBJECTIVE: The objective of this study is to assess the blood requesting and utilization patterns in relation toelective hysterectomies preformed at Saint Paul’s Hospital Millennium Medical College (SPHMMC) in AddisAbaba.METHODOLOGY: A hospital based retrospective study was conducted at SPHMMC from February to March2014. All elective hysterectomies performed in the time period of September 2011 to August 2013 were includedfor the study and the associated blood cross-match ordering and transfusion practice was audited.RESULT: A total of 532 units of blood were cross-matched for the 265 patients who underwent hysterectomies.But, of those only 74 (13.9%) units of blood were transfused to 39 (14.7%) patients. The findings of thisstudy has also shown that for vaginal hysterectomy there is no need to prepare blood while for abdominal hysterectomy,abdominal hysterectomy with salpingo-oophorectomy and de-bulking surgery for ovarian tumourpreparing only a unit of blood is enough.CONCLUSION: The results of the study showed that for most of the elective hysterectomies performed atSPHMMC, the level of blood utilization was minimal and there is significant over ordering of blood and associatedwastage of resources. The process whereby fixed units of blood are requested for every patient irrespectiveof the diagnosis and type of surgical procedure should be revised.KEY WORDS: Surgery, elective hysterectomy, blood transfusion and transfusion indices(Ethiopian Journal of Reproductive Health 2016;8:1